Internal Migration in Nepal and Its Implications on Social Harmony - Thapa , Madhav (Unity Journal, 2025)
The internal migration in Nepal has changed the socio-cultural structure as well as the political demography of Nepal, which has affected communal harmony in Nepali society. The internal migration has diversified Nepali society, and the people of different communities have been sharing common social and cultural values among each other. On the other hand, there are also some implications for social harmony because of internal migration in Nepal. The article is particularly focused on analyzing the implication on social harmony due to internal migration and demographic change. The National Census 2021 indicates that the people of the hills have been continuously migrating towards the Terai region, which has increased the population in Terai, and the population of the hills is rapidly vacating. This internal migration from Hill to Terai has brought regional imbalances and increased the vulnerability of social division in Nepali society. The study follows quantitative as well as qualitative methodology. The primary data were collected from the field study in Ramban and Nagaul villages of the Bara district. The paper analyzes the data of the national census of 2011 and 2021 to study the internal migration from Hill to Terai. The study has found that internal migration has increased population imbalance and criminal activities. It also found that a diversified society is more vulnerable to political exploitation and ethnic and communal clashes, which ultimately threaten social harmony. This article alerts the policymakers regarding the continuous migration from the hill to the Terai region and its implications on social harmony. The demographic change in Nepal due to internal migration has added to the challenge of maintaining social harmony between migrated hill-origin people and Madhesi natives.